Recasts, Uptake, and Noticing - Ellis, Rod; Mifka-Profozic, N. (National Foreign Language Resource Center University of Hawai‘i, 2013)
This volume celebrates the life and groundbreaking work of Richard Schmidt, the developer of the influential Noticing Hypothesis in the field of second language acquisition. The 19 chapters encompass a compelling collection of cuttingedge research studies exploring such constructs as noticing, attention, and awareness from multiple perspectives, which expand, fine tune, sometimes support, and sometimes challenge Schmidt's seminal ideas and take research on noticing in exciting new directions.